2021
DOI: 10.1111/zph.12850
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the emerging multidrug‐resistant Salmonella enterica serotype Kentucky ST314 in China

Abstract: Salmonella enterica serotype Kentucky (S. Kentucky) is an important Salmonella serotype with multiple sequence types (ST) with a worldwide incidence. We identified 8 STs from 180 strains of S. Kentucky, and ST314 emerged as the most commonly encountered ST. Drug susceptibility testing revealed that ST314 had multiple resistance properties, and 75.5% of the strains were resistant to three or more classes of antimicrobials. The rate of resistance to chloramphenicol, florfenicol, sulfafurazole and tetracycline we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For serovar Kentucky-III, most isolates were found in humans, with genomes from one SNP cluster found in cattle and humans and both genomes also typed as ST314 and KCT71, suggesting that they are the same or very closely related strains. ST314 is an emerging Kentucky ST worldwide with reports of isolated strains internationally including Ireland, China and parts of South-East Asia [67][68][69]. Interestingly, a study in Ireland demonstrated that the majority of ST314 strains were isolated in non-human/non-clinical sources, mainly from animal/food sources.…”
Section: Discussionmentioning
confidence: 99%
“…For serovar Kentucky-III, most isolates were found in humans, with genomes from one SNP cluster found in cattle and humans and both genomes also typed as ST314 and KCT71, suggesting that they are the same or very closely related strains. ST314 is an emerging Kentucky ST worldwide with reports of isolated strains internationally including Ireland, China and parts of South-East Asia [67][68][69]. Interestingly, a study in Ireland demonstrated that the majority of ST314 strains were isolated in non-human/non-clinical sources, mainly from animal/food sources.…”
Section: Discussionmentioning
confidence: 99%
“…ST64 was commonly detected in Asian and European patients, and occurs widely in pork from Europe and the USA [40]. ST34 and ST19 were the second and third most common serotypes, respectively, widely found in humans and pigs in Japan, China, the USA, and Europe, indicating that Salmonella may be transmitted from pigs to humans via the food chain [24,41]. Additionally, ciprofloxacinresistant ST314 strains have been increasing since 2014 (from 5.6% in 2014 to 53.2% in 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The recent emergence of concurrent resistance to ciprofloxacin and ceftriaxone among Salmonella isolates is posing a serious threat that requires further monitoring. Another emerging issue related to colistin resistance that was first reported in patients with infection of the Salmonella ST155 strain harboring a colistinresistant mcr-1 gene in China highlights the importance of cautious use and continuous monitoring of colistin resistance in both clinical and veterinary medicines [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…enterica serovar Typhimurium isolated from the environment was from ST34. ST314 has been associated with very high levels of antibiotic resistance (Wang et al 2021), but no resistance was detected in strains isolated in Estonia.…”
Section: Antibiotic Resistance Of Microbesmentioning
confidence: 99%